Passiv in deutschsprachigen Chats. Eine Korpusanalyse. - Vogel, Petra M. (Linguistik Online, 2003)
In this paper I will investigate some passive phenomena in German chat communication including personal and impersonal passive, passive-like constructions and the use of the "dummy" pronoun es. Furthermore, I will compare the results of this study with other empirical works on passive in contemporary German (Brinker 1971 and Schoenthal 1976) thereby discussing whether chat language can be categorized as "spoken German".